Annual Address to the Board of Governors, September 18, 1962 - Black, Eugene R. (World Bank, Washington, DC, 2019)
Eugene R. Black, President of the World Bank, spoke of the record levels for Bank and IDA commitments for economic development projects. More than four-fifths of the amount went to support power and transportation. IDA lent for purposes new to the Bank: municipal water supply, and construction of secondary schools. A new Development Advisory Service operation was created this year. He also discussed IFC’s role in improving the economic growth of the less developed countries via stimulation of private capital markets. He spoke of international trade barriers and terms of trade and their role in the capacity to repay debt. He remarked on the choice between bilateral and multilateral aid, and the influence of politics on development choices. He called for more economic objectivity in aid decisions. He also noted the problem of enlargement of IDA’s resources for the future. He concluded by saying that Bank is showing how an instrument of international cooperation can bring the world's resources to bear on the problems that are of concern to most of mankind--a kind of burning glass that can kindle the fire of hope even in the most remote and forsaken corners of the earth.